Optimizing purchasing decisions through marketing strategies: Case studies in housing property - Abimanyu Tuwuh Sembhodo; Adya Hermawati; Abd Karman; Jana Siti Nor Khasanah; Endang Fatmawati (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This study aims to investigate the influence of digital marketing on purchasing decisions. The research sample in this study is prospective buyers of Griya Citra Perdana Malang Housing. In answering the aim of this study, we used 40 respondents and constructed a simple model based on path analysis. The model built shows that personal selling has no significant effect on purchasing decisions; digital marketing significantly affects purchasing decisions; service quality has a significant impact on purchasing decisions. Furthermore, the simultaneous test shows that the three independent variables significantly influence purchasing decisions.